1995
DOI: 10.1001/archpsyc.1995.03950210068012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alzheimer's Disease and Normal Aging on Cerebrospinal Fluid Norepinephrine Responses to Yohimbine and Clonidine

Abstract: Central nervous system noradrenergic responsiveness is enhanced in normal older subjects, and this age effect is retained in patients with AD. Behavioral sensitivity to increased central nervous system noradrenergic activity is enhanced in patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 54 publications
4
44
0
Order By: Relevance
“…Concentrations of yohimbine and its active metabolite 11-hydroxy-yohimbine in CSF and plasma in these subjects have been reported previously (Peskind et al 1995). In summary, neither the total concentrations of yohimbine plus its active metabolite 11-hydroxy yohimbine nor the concentrations of clonidine differed among groups in either CSF or plasma.…”
Section: Studysupporting
confidence: 64%
See 2 more Smart Citations
“…Concentrations of yohimbine and its active metabolite 11-hydroxy-yohimbine in CSF and plasma in these subjects have been reported previously (Peskind et al 1995). In summary, neither the total concentrations of yohimbine plus its active metabolite 11-hydroxy yohimbine nor the concentrations of clonidine differed among groups in either CSF or plasma.…”
Section: Studysupporting
confidence: 64%
“…Effects of these pharmacologic agents on agitation and blood pressure also were measured. CSF norepinephrine concentrations determined in these studies have been reported previously (Peskind et al 1995;Elrod et al 1997).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…When LC NE outflow is stimulated by yohimbine, AD patients demonstrate robust CSF NE increases that are equivalent to those of normal older patients and substantially greater than in young patients (Peskind et al, 1995); AD patients, but not normal older or young patients, developed agitation symptoms following yohimbine. Studies in postmortem brain tissue demonstrate compensatory changes in brain noradrenergic systems consistent with these clinical research findings.…”
mentioning
confidence: 83%
“…Results of postmortem brain tissue and clinical studies from our laboratory help resolve this paradox (Peskind et al, 1995;Elrod et al, 1997;Szot et al, 2006;Wang et al, 2009).…”
mentioning
confidence: 98%